2021
DOI: 10.3390/antiox10030442
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine Overdose Inducing Hepatic Steatosis and Systemic Inflammation in Both Propacetamol-Induced Hepatotoxic and Normal Mice

Abstract: Acetaminophen (APAP) overdose induces acute liver damage and even death. The standard therapeutic dose of N-acetyl cysteine (NAC) cannot be applied to every patient, especially those with high-dose APAP poisoning. There is insufficient evidence to prove that increasing NAC dose can treat patients who failed in standard treatment. This study explores the toxicity of NAC overdose in both APAP poisoning and normal mice. Two inbred mouse strains with different sensitivities to propacetamol-induced hepatotoxicity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…From Table 1 evidence, it was clear that most RCTs reported on the therapeutic effects of NAC against paracetamol overdose. This is consistent with overwhelming literature that has been published over the years [ 20 , 85 , 86 ], supporting the use of NAC to protect against liver injury that is consistent with paracetamol intoxication. For example, in an RCT conducted between 1996 and 1999, Yip and Dart [ 87 ] showed that an NAC loading dose of 140 mg/kg body weight, given in a 20 h period, was effective in preventing hepatic injury after an acute acetaminophen overdose, especially in patients with an acetaminophen level below the probable hepatotoxicity line.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurysupporting
confidence: 88%
See 1 more Smart Citation
“…From Table 1 evidence, it was clear that most RCTs reported on the therapeutic effects of NAC against paracetamol overdose. This is consistent with overwhelming literature that has been published over the years [ 20 , 85 , 86 ], supporting the use of NAC to protect against liver injury that is consistent with paracetamol intoxication. For example, in an RCT conducted between 1996 and 1999, Yip and Dart [ 87 ] showed that an NAC loading dose of 140 mg/kg body weight, given in a 20 h period, was effective in preventing hepatic injury after an acute acetaminophen overdose, especially in patients with an acetaminophen level below the probable hepatotoxicity line.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurysupporting
confidence: 88%
“…Because of its strong antioxidant properties and its known capacity to enhance intracellular GSH levels, N-acetyl cysteine (NAC) has attracted a lot of interest as a therapeutic agent against diverse diseases [16][17][18][19], besides being a drug of choice to protect against paracetamol-induced liver injury [19]. In addition to enhancing GSH levels, recent developments suggest NAC can modulate other mechanisms of oxidative stress, including reducing endoplasmic reticulum stress (ER) or improving mitochondrial function, to protect against liver injury [20,21]. Thus, the current review explores mechanisms of oxidative stress implicated in the development of DILI.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of NAC overdose has not yet been defined for patients with paracetamol overdose or for healthy people using single or repeated doses of NAC [ 29 ]. It has been reported that an overdose of NAC (100 g) in a short time can cause hemolysis, thrombocytopenia, acute renal failure, and death in patients with glucose-6-phosphate dehydrogenase (G6PD) normal.…”
Section: Pharmacokinetics and Bioavailabilitymentioning
confidence: 99%
“…The reported case resulted from an error during the administration of the loading dose of NAC for the treatment of paracetamol overdose, which should be 10 g (10,000 mg) [ 30 ]. Toxicity data for NAC in animals are available [ 29 ]. Box 1 provides a summary of the main characteristics of NAC.…”
Section: Pharmacokinetics and Bioavailabilitymentioning
confidence: 99%
“…CYP2E1, a cytochrome 450 (CYP450) involved in drug-induced liver injury, is predominantly expressed in the liver [ 45 , 46 ]. Although NAC has been considered a standard therapeutic agent for relieving acetaminophen poisoning, there still exist certain limitations for its use due to the possibility of inducing hepatic steatosis and systemic inflammation [ 47 ]. Several studies have investigated the efficacy of Hyp in reducing hepatotoxicity in mice and liver cells suffering from drug-induced liver injury [ 48 , 49 , 50 , 51 ].…”
Section: Pharmacological Effects Of Hyperoside In Liver Diseasesmentioning
confidence: 99%